2010
DOI: 10.2215/cjn.05410709
|View full text |Cite
|
Sign up to set email alerts
|

Low Dietary Sodium Intake Increases the Death Risk in Peritoneal Dialysis

Abstract: Background and objectives: To explore the correlation between dietary sodium intake and cardiovascular and overall mortality, and then determine whether this correlation can be explained by protein and energy intake paralleled with sodium intake in dialysis patients.Design, setting, participants, & measurements: This single-center retrospective cohort study enrolled 305 incident patients who started peritoneal dialysis in our unit from July 2002 to February 2007. All patients were followed until death or until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 36 publications
6
68
2
Order By: Relevance
“…[8][9][10] Concerns about low-salt diets were first raised by Meneely et al 13 and Dahl and Love, 14 who linked decreased salt intake to growth failure and increased mortality in rats. Dong et al 15 revealed that low dietary salt intake independently predicts the high overall and cardiovascular mortality of dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Concerns about low-salt diets were first raised by Meneely et al 13 and Dahl and Love, 14 who linked decreased salt intake to growth failure and increased mortality in rats. Dong et al 15 revealed that low dietary salt intake independently predicts the high overall and cardiovascular mortality of dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…One of the studies that used food records also asked participants to alter their diet to facilitate measurement of Na intake. 65 Although most studies did not provide the level of information required to assess whether systematic error was present, we identified evidence of it in 1 study that used 24-hour urine collections and in 5 that used dietary surveys. One study showed evidence of undercollection of 24-hour urine samples: In men, creatinine excretion levels differed by 24.8% between the lowest and highest tertiles of Na intake, whereas weight differed by just 9.8% in these tertiles 47 ( Figure; online-only Data Supplement Table 2a).…”
Section: Domain 1: Errors With the Greatest Potential To Alter The DImentioning
confidence: 99%
“…8,26,27 There is no metabolic or pathological reason for not giving a standard energy intake to stable adult maintenance dialysis patients. Indeed, their metabolic needs, based on resting energy expenditure, are similar to those of normal adults, that is, 35 kcal/kg BW/day.…”
Section: Discussionmentioning
confidence: 99%